Painful Diabetic Neuropathy in Clinical Practice - Boulton, Andrew J.M.; Vileikyte, Loretta; SpringerLink (Online service) (London : Springer London, 2011)
Painful Diabetic Neuropathy in Clinical Practice provides a concise, didactic and essential resource for clinicians in the management of neuropathic pain in diabetic patients. This volume opens with overviews of epidemiology, classification and clinical features, including a discussion of the negative effect of painful neuropathic symptoms on quality of life. These are followed by a chapter on diagnosis and staging, which includes approaches to history taking, clinical examination, pain assessment scales, testing and staging. The book concludes with a chapter on the various approaches in the management of neuropathic pain, including the most up-to-date guidelines on the pharmacological treatment of this condition. This concise handbook is an invaluable reference for primary care practitioners and diabetologists who wish to keep up to date with the diagnosis and management of neuropathic pain.
Introduction to Diabetic Neuropathies -- Classification and Clinical Features -- Diagnosis and Staging -- Management of Neuropathic Pain.
Keywords: Medicine; Internal medicine; Diabetes; Endocrinology; Medicine & Public Health; Diabetes; Endocrinology; Internal Medicine